Évaluer le prix de la main-d'œuvre sur les chantiers de construction du duché d'Alençon au xve siècle - Marie-Anne Moulin (Les Cahiers de Framespa)
The study of salaries and camp (in cash and in kind) on the construction sites of the Duchy of Alençon in the 15th century has extensive documentary coverage that allows a comparison according to the building site, the authority and the building profession. Indeed, the ducal, hospital and parish sources, largely edited, highlight variable pay practices in the territory. A hierarchy of salaries between cities and between building professions also emerges. These observations lead to several questions. The first one is to know what is included in the notion of salary and whether the definition is the same throughout the duchy. To explain these wage disparities, however, it is also important to examine those who set wages and the elements they used to assess them. It is also important to wonder why regional variations were not the only ones, as there were variations within the same city and the same occupation.building sites, salary, supplementary salary